(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To describe the characteristics of age, sex; histopathology; some paraclinical features and to evaluate the concentration of Prostaglandin E2 in two groups of patients with polyps and colorectal cancer (CRC). Methods: Cross-sectional descriptive study on 308 patients: including 149 CRC patients and 109 patients with colorectal polyps diagnosed by cytology or histopathology, 50 healthy individuals; who were examined and treated at Military Hospital 175. Results: The mean age in the CRC group was 59,64 ± 11,66; in the colorectal polyps group was 58,45±9,65; in the healthy group was 57,32±8,17; there was no difference in age between the study groups. The incidence is higher in men than in women, and this difference is statistically significant (p=0,0061). Adenocarcinoma is dominant in CRC patients (77,85%); for polyps, adenomas are dominant (83,49%). The mean PGE2 concentration in CRC patients was 7,86±2,8 pg/ml; in polyp patients was 5,29±1,3 pg/ml; in healthy people it was 2,78±0,5 pg/ml. Conclusions: There was no difference in the concentration of PGE2 in the polyp and CRC groups (p>0,05). However, there was a significant difference in PGE2 levels in the two groups of cancer and colorectal polyps compared to healthy individuals (p< 0,05 (0,0021)).